Analysis of village budget use in improving the welfare of the dides community Ajatikecamansaguling regency, West Bandung regency - Syahrul Ramadan; Muhammad Sugiharto (Sean Institute, 2024)
In improving the welf are of the community in Jati Village, it is necessary toproperly utilize the village budget. The purpose of this research is to beable to find out how the village fund budget is utilized and how much influence it has in improving people's welfare. This study uses qualitative method swith data collection techniques, namely interviews, observation, documentation and literature studies, with 74 respondents using the slovin formula from a population of 284 people.The processof managing Village Fund Allocation (ADD) in improving the welf are of the community in Jati Village is through the stage so planning, implementing, monitoring, and accountability for village fundal locations. The use of Village Fund Allocation (ADD) in improving the we lfare of the people in Jati Village has under gonemany change sand in the implementation of development activities it can be seen from the extent to which it is in accordance with what has been built. Increasing the level of welfare through the allocation of village funds is great increased as long as there is development that is going well. All of these processes are carrie doutby the village government accompany ied by the sub-districtas sistance team and carry out their dutie sproperly. In this case the development of village facilities and infrastructure as well as community empowerment is good. It can be concluded that the use of the village fund budget in Jati Village has had ago dimpact on the village community.